Kajian Ajaran Sesat dalam Pengajian Islam: Satu Sorotan - Engku Alwi, Engku Ahmad Zaki (Jurnal Usuluddin, 2007)
The article reviews the historical background and literature on cultism in Malaysia. The problem relating to cultism needs to be urgently addressed as it directly affects Islamic theology and Muslims. This scenario has raised the importance research in the field of cult movement in Islamic studies.